STRATEGI COPING MAHASISWA UIN SUNAN KALIJAGA S2 MPAI 1C DALAM MENGELOLA STRES AKADEMIK - Selvia Yolanda; Mia Rosiana Mahmudah; Suhaimi (Prodi Bimbingan dan Konseling Islam, 2026)
This study is motivated by the high academic demands faced by first-semester Master’s students in Islamic Education (PAI), who are required to adapt to an intensive learning rhythm, complex theoretical readings, and dual roles as both students and working professionals. The objectives of this study are to examine: (1) the forms of academic stress experienced by first-semester PAI Master’s students in Class C; (2) the sources and contributing factors of their academic stress; and (3) the coping strategies employed to manage academic stress. This research adopts a descriptive qualitative approach using purposive sampling, involving a number of Master’s students in Islamic Education Class C who have direct experience with academic stress. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive analysis model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the forms of academic stress experienced by the students include emotional symptoms (anxiety, fear of incompetence, and feelings of inferiority), physical symptoms (sleep disturbances, fatigue, and headaches), and behavioral symptoms (procrastination, difficulty concentrating, and task avoidance). The primary sources and contributing factors of academic stress stem from heavy coursework and reading loads, adaptation to lecturers’ teaching styles and expectations, dual roles as students and workers, internal factors (perfectionism and self-doubt), as well as expectations of religious commitment as Islamic Education students. The coping strategies employed are integrative in nature, combining problem-focused coping (such as scheduling and prioritization, and seeking academic support), emotion-focused coping (sharing concerns, resting, and engaging in enjoyable activities), and spiritual coping (prayer, ritual worship, Qur’anic recitation, remembrance of God, and trust in God). These findings highlight the importance of strengthening academic management skills, emotional regulation, and spiritual mentoring to support the adaptation of first- semester Master’s students in Islamic Education.